Endobronchial Migration of a POD Packing Coil Following Embolization of a Pulmonary Artery Pseudoaneurysm - McLaughlin, Joseph N.; Lamus, Daniel; Hegde, Siddhi; Kalva, Sanjeeva P. (Seminars in Interventional Radiology, 2023)
The authors report a case of endobronchial migration of a POD packing coil following embolization of a pulmonary artery pseudoaneurysm in a patient with cavitary tuberculosis and its successful management by bronchoscopy-assisted removal of the coil. Coil migration may be secondary to continued cough and persistence of a bronchial to pulmonary artery fistula from tuberculous infection and inflammation.
Keywords: endobronchial migration; pulmonary artery embolization; POD packing coil; pseudoaneurysm; bronchoscopy; interventional radiology